Fingolimod effects in neuroinflammation: Regulation of astroglial glutamate transporters? - Lee, De-Hyung; Seubert, Silvia; Huhn, Konstantin; Brecht, Lukas; Rötger, Caroline; Waschbisch, Anne; Schlachetzki, Johannes; Klausmeyer, Alice; Melms, Arthur; Wiese, Stefan; Winkler, Jürgen; Linker, Ralf (PLoS ONE, 2017)
Fingolimod is an oral sphingosine-1-phosphate-receptor modulator which reduces the recirculation of immune cells and may also directly target glial cells. Here we investigate effects of fingolimod on expression of astroglial glutamate transporters under pro-inflammatory conditions. In astrocyte cell culture, the addition of pro-inflammatory cytokines led to a significant downregulation of glutamate transporters glutamate transporter-1 (slc1a2/SLC1A2) and glutamate aspartate transporter (slc1a3/SLC1A3) expression on the mRNA or protein level. In this setting, the direct application of fingolimod-1 phosphate (F1P) on astrocytes did not change expression levels of slc1a2 and slc1a3 mRNA. The analysis of both transporters on the protein level by Western Blot and immunocytochemistry did also not reveal any effect of F1P. On a functional level, the addition of conditioned supernatants from F1P treated astrocytes to neuronal cell culture did not result in increased neurite growth. In experimental autoimmune encephalomyelitis as a model of multiple sclerosis, fingolimod treatment reduced T cell and macrophages/microglia mediated inflammation and also diminished astrocyte activation. At the same time, fingolimod restored the reduced expression of slc1a2 and slc1a3 in the inflamed spinal cord on the mRNA level and of SLC1A2 and SLC1A3 on the protein level, presumably via indirect, anti-inflammatory mechanisms. These findings provide further evidence for a predominantly peripheral effect of the compound in neuroinflammation.
EVALuna2:22494